The First Genetic and Comparative Map of White Lupin (Lupinus albus L.): Identification of QTLs for Anthracnose Resistance and Flowering Time, and a Locus for Alkaloid Content - Phan, H.; Kedar, A.; Ellwood, Simon; Nelson, M.; Oliver, Richard (2007)
We report the first genetic linkage map of white lupin (Lupinus albus L.). An F8 recombinant inbred line population developed from Kiev mutant × P27174 was mapped with 220 amplified fragment length polymorphism and 105 gene-based markers. The genetic map consists of 28 main linkage groups (LGs) that varied in length from 22.7 cM to 246.5 cM and spanned a total length of 2951 cM. There were seven additional pairs and 15 unlinked markers, and 12.8% of markers showed segregation distortion at P < 0.05. Syntenic relationships between Medicago truncatula and L. albus were complex. Forty-five orthologous markers that mapped between M. truncatula and L. albus identified 17 small syntenic blocks, and each M. truncatula chromosome aligned to between one and six syntenic blocks in L. albus. Genetic mapping of three important traits: anthracnose resistance, flowering time, and alkaloid content allowed loci governing these traits to be defined. Two quantitative trait loci (QTLs) with significant effects were identified for anthracnose resistance on LG4 and LG17, and two QTLs were detected for flowering time on the top of LG1 and LG3. Alkaloid content was mapped as a Mendelian trait to LG11.